Implementasi Analisis Swot dalam Perencanaan Peningkatan Mutu Pendidikan di Sekolah Dasar - Eneng Garnika; Baiq Rohiyatun; Lu’luin Najwa (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study is to describe, 1) the implementation of SWOT analysis in improving the quality of education in elementary schools; 2) supporting factors, and inhibiting SWOT analysis; 3) strategies for improving the quality of education by schools. This research method is descriptive qualitative with case study design. Collecting research data using observation, interviews, and documentation studies and then analyzed using data triangulation. The results of the SWOT analysis at SDN 7 Mataram are a) strengths, namely the first strategic location of the school (in downtown Mataram). second, the condition and completeness of good facilities and infrastructure; third, human resources (educators and education personnel have qualifications; fourth, a conducive, comfortable and beautiful school climate. Fourth, the fifth standard of the learning process, assessment standards are coordinated with parents and guardians of students; b) Weaknesses, namely from the external environment, namely the lack of concern for parents for the school environment; c) opportunities, namely student guardians facilitate the needs of students in terms of academic and non-academic, students have talents and achievements that often win competitions at the city and provincial level, relations with residents around the school run well and harmoniously; d) treaths (challenges), namely guardians of students who are very critical of the development of students so that teachers must be wiser in making decisions and attitudes. In conclusion, the supporting factors for implementing the SWOT analysis in SDN are human resources, namely stakeholders who are proactive in providing information, and carry out progressive development and principals in school evaluation and development, and strategic planning. The inhibiting factor for implementing the SWOT analysis in SDN is the lack of community support and public understanding of school management. Strategies to improve the quality of education at SDN 7 Mataram by increasing the Koran program, strengthening character education, adding extracurricular activities, creating excellent activities with school characteristics, and strengthening student counseling. Keywords: SWOT Analysis, Implementation, Quality of Education